2020
DOI: 10.1111/1745-5871.12399
|View full text |Cite
|
Sign up to set email alerts
|

A social practice perspective on meat reduction in Australian households: Rethinking intervention strategies

Abstract: Recent widespread calls and strategies for consumers to change and reduce meat consumption position meat as both an environmentally unsustainable and highly desired food. Such change is often understood as an unattractive and difficult process of relinquishment, and that perspective informs interventions designed to lessen the presumed hardship involved. This article troubles such assumptions by reference to a practice theoretical approach and by extending conceptual debates circulating within consumption geog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Among other studies, recent qualitative research, e.g., [6,9,10], stresses the impact of the social context as a barrier to reducing meat consumption. The current study confirmed this.…”
Section: Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among other studies, recent qualitative research, e.g., [6,9,10], stresses the impact of the social context as a barrier to reducing meat consumption. The current study confirmed this.…”
Section: Opportunitiesmentioning
confidence: 99%
“…Even though the field of meat reduction and flexitarianism has blossomed in recent years [5], this does not imply that it has reached a stage that leaves room only for quantitative studies. Recent qualitative studies [6][7][8][9][10][11] prove that interview-based research produces insightful results, highlighting mundane barriers or ordinary facilitators in the process of lowering meat consumption. Such everyday difficulties or possibilities are frequently situated in the domains of capabilities and opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…This paper can be understood as part of an emerging body of work that treats food consumption as more than a social and cultural practice, also addressing the material and embodied nature of food practices (Daly 2020;Neuman 2019). This approach, at times referred to as post-human (Daly 2020), socio-material (Domaneschi 2019), or material-semiotic (Evans 2020) practice theory, allows us to offer a different, but complementary, explanation as to how plant-based consumption is increasingly becoming possible.…”
Section: Discussionmentioning
confidence: 99%
“…Moving beyond a narrow focus on food itself, our approach broadens this scope to include the multiple material elements making up the socio-material landscape that enables and shapes plant-based consumption. This broader approach is also accompanied by a move away from examining vegan eating (Twine 2017a), or mealing-practice (Daly 2020), toward bundles of plant-based shopping, cooking, and eating practices.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are new tendencies, and some segments currently privilege healthy [ 1 ] and sustainable characteristics [ 2 ]. Food consumption has several dimensions, including that of a social and cultural magnitude, and this sometimes compromises policies to change unadjusted behaviours [ 3 ] and influence food perceptions [ 4 ]. The sociodemographic and behavioural factors also have their implications [ 5 ] on consumer behaviour.…”
Section: Introductionmentioning
confidence: 99%